Координационная химия солевых расплавов - Волков Сергей Васильевич (Наукова думка, 1977)
Экземпляры: КХ (20150226) / Инвентарный номер: 677737 / Цена: 3.70 / Сис.шифр: 546 / Авт.знак: В 67 / ГРНТИ: 31 / ББК: 24